Efektivitas Penggunaan Aplikasi Kasda Online dalam Transaksi Dana Desa - ridwan ridwan; Isnaini Tolas; Sri Murni (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2023)
Advances in technology provide many conveniences to the community, one of which is the Online Regional Cash (KASDA) application. The Kasda Online application is an application intended for each village as a tool for conducting village fund transactions in North Sulawesi. This application was developed by PT Bank SulutGo. This study aims to discover how effective the use of the Kasda Online application is in village fund transactions in the Tutuyan sub-district, East Bolaang Mongondow Regency. The method used in this research is descriptive qualitative method. The data analysis techniques used in this study were data reduction, data presentation and data classification, while data collection used observation, interview, and documentation methods. Based on the results of the study, it shows that the Kasda Online of Bank Sulut-Go in Tutuyan sub-district, East Bolaang Mongondow Regency has not been used effectively and there are still several obstacles in operating it including inadequate human resources, and weak commitment and role of the provincial and district governments in overseeing the use of the Kasda Online application in their area.